2010
DOI: 10.3233/wia-2010-0184
|View full text |Cite
|
Sign up to set email alerts
|

HITS algorithm improvement using semantic text portion

Abstract: Kleinberg's Hypertext-Induced Topic Selection (HITS) algorithm is a popular and effective algorithm to rank web pages. One of its problems is the topic drift problem. Previous researches have tried to solve this problem using anchor-related text. In this paper, we investigate the effectiveness of using Semantic Text Portion for improving the HITS algorithm. In detail, we examine the degree to which we can improve the HITS algorithm. We also compare STPs with other kinds of anchorrelated text from the viewpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We set 2, 3 and 4 as the overlap threshold (In our prior work [8], we have found that the performance of the proposed method is very low when the overlap threshold is 1 under the influence of clustering method based on modularity). We conduct nine threshold conditions (clique threshold, overlap threshold) = (3, 2), (4, 2), (4, 3), (5, 2), (5,3) and (5,4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We set 2, 3 and 4 as the overlap threshold (In our prior work [8], we have found that the performance of the proposed method is very low when the overlap threshold is 1 under the influence of clustering method based on modularity). We conduct nine threshold conditions (clique threshold, overlap threshold) = (3, 2), (4, 2), (4, 3), (5, 2), (5,3) and (5,4).…”
Section: Methodsmentioning
confidence: 99%
“…Jiang and Conrath measured the similarity between words using link information and semantic information of words [7]. Hung et al improved the HITS algorithm by analyzing anchor text [5].…”
Section: Related Workmentioning
confidence: 99%
“…Equation ( 1) illustrate that if a page which be pointed by many hub, the weight can be increased. Equation (2) illustrate that if a page pointed to authority page, the hub weight can also be increased.…”
Section: The Basic Think Of Hitsmentioning
confidence: 99%
“…Otherwise, the existing methods have the character of computing simple and objectiveness. For example, the HITS algorithm exist evident shortage, first of all, the algorithm only using the link structure to consider the importance of web cite or web page, while exception for the web page link structure, according to the practice, the content of web cite is the other very important factor to authorities cite [2] . Secondly, other type of link includes links that do not convey people's opinions such as automatically generated links, links for navigation, and banner ads.…”
Section: Introductionmentioning
confidence: 99%